Acceptance and barriers of COVID-19 vaccination among people with chronic diseases in Saudi Arabia - Amjad Ahmed Alghamdi; Methail Saleh Aldosari; Ruby Ali Alsaeed (Journal of Infection in Developing Countries)
Introduction: Coronavirus Disease 2019 is a life-threatening disease, especially for people suffering from chronic diseases. As the vaccine is considered an essential tool to confront pandemics, many international medical institutions have developed vaccines. Countries around the world started immunizing their citizens. This study aims to assess the acceptance and barriers of COVID-19 vaccine uptake among Saudi Arabian people who suffer from chronic diseases.